Thermoluminescence of natural quartz - Lontsi Sob, Aaron Joel (Rhodes University, Faculty of Science, Department of Physics and Electronics, 2014)
The kinetic and dosimetric features of the main thermoluminescence peak of quartz have been investigated in unannealed as well in quartz annealed at 500ËšC for 10 minutes. The main peak is found at 92 and 86ËšC respectively for aliquots of unannealed and annealed samples irradiated to 10 Gy and heated at 5.0ËšC/s. For each sample, the intensity of the main peak is enhanced with repetitive measurement whereas its maximum temperature is unaffected. The peak position of the main peak in each sample is independent of the irradiation dose and this, together with its fading characteristics are consistent with first-order kinetics. For low doses, typically between 2 and 10 Gy, the dose response of the main peak in each sample is linear. In the intermediate dose range from 10 to 60 Gy, the growth of the main peak in each sample is sub-linear and for greater doses, in the range from 60 Gy to 151 Gy, it is linear again. The half-life of the main peak of the unannealed sample is about 1.3 h whereas that of the annealed sample is about 1.2 h. The main peak in each sample can be approximated to a first-order glow peak. As the heating rate increases, the intensity of the main peak in each sample decreases. This is evidence of thermal quenching. The main peak in each sample is the only peak regenerated by phototransfer. The resulting phototransferred peak occurs at the same temperature as the original peak and has similar kinetic and dosimetric features. For a preheat temperature of 120ËšC, the intensity of the phototransferred peak in each sample increases with illumination time up to a maximum and decreases afterwards. At longer illumination times (such as 30 min up to 1 h), no further decrease in the intensity of the phototransferred peak is observed. The traps associated with the 325ËšC peak are the main source of the electrons responsible for the regenerated peak. Radioluminescence emission spectra were also measured for quartz annealed at various temperatures. Emission bands in quartz are affected by annealing and irradiation. A strong enhancement of the 3.4 eV (~366 nm) emission band is observed in quartz annealed at 500ËšC. A new emission band which grows with annealing up to 1000ËšC is observed at 3.7 eV (~330 nm) for quartz annealed at 600ËšC. An attempt has been made to correlate the changes in radioluminescence emission spectra due to annealing with the influence of annealing on luminescence lifetimes in quartz.
Keywords: Thermoluminescence; Quartz; Thermoluminescence dosimetry